MANAJEMEN MUTU DALAM MENINGKATKAN PROFESIONALISME GURU DI MTS MUHAMMADIYAH 15 MEDAN - Irwansyah, Irwansyah; Fahada, Nazli (UIN Sumatera Utara Medan, 2024)
This research aims to determine Quality Management in Increasing Teacher Professionalism at MTS Muhammadiyah 15 Medan. The research method used is a qualitative method. Data collection techniques include observation, interviews and documentation with emphasis on informant data sources: madrasah principals, deputy madrasah principals and teachers to confirm the validity of the data obtained. The results of this research reveal three findings, namely: (1) To find out Quality Management in Improving Teacher Professionalism at MTS Muhammadiyah 15 Medan, (2) To find out the steps taken by madrasah heads in Quality Management in Increasing Teacher Professionalism at MTS Muhammadiyah 15 Medan (3 ) To find out the obstacles of madrasa heads in Quality Management in Increasing Teacher Professionalism at MTS Muhammadiyah 15 Medan. From the explanation above, it can be concluded that quality management in improving teacher professionalism carried out by madrasah heads starts from planning such as the process of selecting teachers in recruitment then carrying out organizing such as empowering the competencies possessed by teachers, and also placing teachers according to their majors and competencies, after It coordinates Teacher Working Groups (KKG), holds education and training (diklat), Subject Teacher Conferences (MGMP), and involves teachers in Quality Management in Increasing Teacher Professionalism at MTS Muhammadiyah 15 Medan.